Design of an Optimum Battery Electric Fishing Vessel for Natuna Sea - Juniarko Prananda; Eddy Setyo Koenhardono; Rivaldi Clarence Tjoa (Institut Teknologi Sepuluh Nopember, 2019)
Natuna Sea is one of the places in Indonesia, which has a high potency of fish up to one million ton per year. Fisherman in Indonesia relies too much on the fossil fuel, which has limited resources. The author wants to redesign the fishing vessel into the battery electric fishing vessel that can be recharge to reduce the use of fossil fuel and also to increasing the revenue of the fisherman. To minimize the capacity of the battery, the fishing activities concept is also change into centralized fishing activities which the activities is centralized in an open sea and has the offshore building as the fishing base that has power station to recharge the batteries and cold storage to collect all the fishes. As the object to redesign, it is used 10 GT purse seine fishing vessel. As the results of the calculation, it gets the total battery capacity 6000 Ah for operation 11 hours (4 hours travel time, 6.5 hours fishing activities, and 0.5 hours break). Based on the technical and economic analysis, it can be concluded that the battery electric fishing vessel has a better revenue and fewer expenses than the diesel-powered fishing vessel.